Booster dose of mRNA vaccine augments waning T cell and antibody responses against SARS-CoV-2 - Özbay Kurt, Feyza Gül; Lepper, Alisa; Gerhards, Catharina; Roemer, Mathis; Lasser, Samantha; Arkhypov, Ihor; Bitsch, Rebekka; Bugert, Peter; Altevogt, Peter; Gouttefangeas, Cécile; Neumaier, Michael; Utikal, Jochen; et al. (Frontiers in Immunology, 2022)
A gradual decay in humoral and cellular immune responses over time upon SARS-CoV-2 vaccination may cause a lack of protective immunity. We conducted a longitudinal analysis of antibodies, T cells, and monocytes in 25 participants vaccinated with mRNA or ChAdOx1 up to 12 weeks after the 3rd (booster) dose with mRNA vaccine. We observed a substantial increase in antibodies and CD8 T cells specific for the spike protein of SARS-CoV-2 after vaccination. Moreover, vaccination induced activated T cells expressing CD69, CD137 and producing IFN-γ and TNF-α. Virus-specific CD8 T cells showed predominantly memory phenotype. Although the level of antibodies and frequency of virus-specific T cells reduced 4-6 months after the 2nd dose, they were augmented after the 3rd dose followed by a decrease later. Importantly, T cells generated after the 3rd vaccination were also reactive against Omicron variant, indicated by a similar level of IFN-γ production after stimulation with Omicron peptides. Breakthrough infection in participants vaccinated with two doses induced more SARS-CoV-2-specific T cells than the booster vaccination. We found an upregulation of PD-L1 expression on monocytes but no accumulation of myeloid cells with MDSC-like immunosuppressive phenotype after the vaccination. Our results indicate that the 3rd vaccination fosters antibody and T cell immune response independently from vaccine type used for the first two injections. However, such immune response is attenuated over time, suggesting thereby the need for further vaccinations.